(The Effect of Fish Meat Tapioka Ratio and Drying Method on Quality of Eastern Little-Tunas (Euthynus Affinis) Cracker Produced by the Intermediate Technology) - Supriatna, Dadang; Enie, A. Basrah; Moelyana, Betty D.S; Suhara, Otong (Balai Besar Industri Agro, 1995)
The effect of fish meat-tapioca ratios and drying methods on the quality of eastern-little-tunas (Euthynnus affinis)crakers produced by the intermediate tecnology has been studied.The ratio of fish meat and tapioca used were 30:70,40:60,50:50,60:40,70:30,while drying method was sun drying and oven driyng. The result showed that the 30:70 ratio with oven drying resulted in the highest mean value of acceptability (taste,aroma,apperance,crispiness,linear expansion) and the protein content met the requirement of the Indonesian Industrial Standard for fish crakers.Â